Hustle Culture and Workplace Anxiety: The Psychological Effect of Overworked Behavior among Working Individuals - Regmi, Ruchee; Manandhar, Siddika (DAV Research Journal, 2025)
This study investigates how “hustle culture” behaviors, which include intense work participation, high internal motivation, and a strong desire for job satisfaction, impact anxiety levels among working professionals in the Kathmandu Valley of Nepal. Understanding the psychological effects of these behaviors is crucial for boosting employee well-being and organizational productivity, especially as they become more prevalent. The effect of hustling culture behaviors on anxiety in Nepali workers was investigated utilizing a cross-sectional, causal study design and a quantitative approach. SPSS version 20 was used to analyze data collected from 226 working participants using a structured questionnaire. Results show a substantial positive connection between hustle-culture behaviors and anxiety among Nepali workers. Participants with moderate to high levels of work participation, self-driven motivation, and job happiness also reported higher levels of anxiety. Job satisfaction can lead to emotional distress due to over commitment and internal pressure, despite its normally positive impact on well-being. Research indicates that high levels of job commitment and self-imposed performance pressure might increase employee anxiety. Even job happiness, when combined with extreme devotion, can worsen mental stress. Effective task management and proactive recovery assistance are critical to reducing anxiety and fostering healthy workplace dynamics. This study applies the Job Demands-Resources (JD-R) Model to the Nepali workplace, including hustle-culture dynamics into existing occupational stress theories. It provides practical ideas for Nepali organizations, including integrating mental health care, fostering work-life balance, and setting reasonable performance targets to improve long-term productivity and employee well-being.